Development and application of a biocatalyst-filter reactor for the continuous production of caseinate hydrolysate surfactants. (September 2018) - Ewert, Jacob; Horstmann, Gudrun; Glück, Claudia; Claaßen, Wolfgang; Stressler, Timo; Fischer, Lutz
Graphical abstract: Highlights: Casein hydrolysis is feasible with an immobilized peptidase in a biocatalyst-filter reactor. Continuous operating time of 24 days without microbial contamination was achieved. Space-time yield was increased by 56% compared to the batch process. Produced hydrolysate was improved in its foaming and emulsifying behaviour. Abstract: A novel continuous process for enzymatic production of sodium caseinate hydrolysates with a low degree of hydrolysis (DH) and increased interfacial behaviour was developed. Retention of free peptidase in the reactor (separation of the peptidase from the product via an ultra-filtration membrane) was not possible because the peptidase used (thermolysin-like peptidase from Geobacillus stearothermophilus ; Sternzym BP 25201; 34 kDa, approximately 4.3 nm) was smaller than the hydrolysate product (up to 90 μm). Thus, the peptidase was immobilized on macroporous particles (Sepabeads EC-EP/M; 200–500 μm) and applied for the process consisting of a stirred reactor vessel and a metal filter (150 μm) as the separation unit. A consistent DH of 2.2–2.6% was obtained by adding about 1/3 of the initial peptidase activity per day or adjusting the residence time. This DH resulted in improved foam and emulsion behaviours (foam stability increased to 139 ± 2.3%; emulsion stability increased to 162 ± 9%) of the filtrate compared to substrate and was like a hydrolysate produced in a batch hydrolysis using the free enzyme. However, the continuous process was superior to the batch process because it resulted in an increased space-time yield (155%) and enzyme productivity (695%).